Does rice straw addition and/or Vallisneria natans (Lour.) planting contribute to enhancement in nitrate nitrogen and phosphorus removal in constructed wetlands under low temperature?. (April 2022) - Cui, Naxin; Zhang, Xu; Cai, Min; Chen, Guifa; Zhou, Li; Zou, Guoyan
Graphical abstract: Highlights: CWs with rice straw added in water achieved the highest N removal rates. Microbial denitrification accounted for reduction in over 70% of influent TN load. Rice straw, vegetation and their combination improved P removal in CWs. Adding method caused different bacterial biodiversity in the rice straw biofilms. Abstract: It is a global concern that nitrogen and phosphorus removal performances of constructed wetlands (CWs) are limited during cold weather. This study analyzed nutrient removal efficiencies and mechanisms in six CWs including combinations between evergreen submerged vegetation planting and rice straw adding under low temperature. The results showed that both unvegetated and vegetated CWs achieved the highest removal rates of total nitrogen (TN) (85.1–86.6%) and NO3 – -N (98.2–98.7%) with increases of approximately 56% and 68% by adding rice straw in water, respectively. Moreover, microbial denitrification accounted for reduction in over 70% of influent TN load. Planting vegetation, adding rice straw or their combination could all improve total phosphorus removal. Compared with adding rice straw in sediment, more diversifying bacterial community and higher abundances of some anaerobic fermentative species in the rice straw biofilm might have contributed to higher nitrogen removal in CWs with rice straw added in water.